Contact Toxicity Effects of Selected Organic Leaf Extracts of Tithonia diversifolia (Hemsl.) A. Gray and Vernonia lasiopus (O. Hoffman) against Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) - Gitahi, Stephen Maina; Ngugi, Mathew Piero; Mburu, David Nganga; Machocho, Alex Kingori (International Journal of Zoology, 2021)
Maize weevil (Sitophilus zeamais) infestation results in a substantial reduction in the quantity and deterioration of the quality of stored maize. Most farmers control weevils using conventional pesticides which are usually associated with several human health risks as well as intoxication of the fauna and flora. However, bioinsecticides form an alternative intervention since they possess fewer side effects on human health, are ecofriendly, and are readily available. This study sought to validate and document, in a systematic way, the pesticidal properties of the species Tithonia diversifolia and Vernonia lasiopus used for many years by many people of the world on S. zeamais. The plant leaf samples were obtained from Embu County, Kenya. Dichloromethane and ethyl acetate solvents were used to extract active phytochemicals from the dried plant sample powder. The GC-MS analysis of the obtained extracts was performed at ICIPE laboratories to identify their phytochemical compositions. Twenty grams of maize grains were put in 50 ml plastic vials and admixed with different treatments. The positive control group was treated with Actellic Super™, while the negative control was treated with the respective extracting solvent only. The experimental groups were separately treated with the plant leaf extracts at doses of 25, 50, 75, and 100%. After treatment, each of the six groups was infested with 10 male S. zeamais and weevil mortality as a result of contact toxicity of the treatments was assessed at 6, 24, 48, 72, and 96 hours after the insects were exposed to the extracts. Results of the study indicate that the selected organic leaf extracts of T. diversifolia and V. lasiopus possessed significant contact insecticidal effects that ranged between 1.67 to 99.98%. Furthermore, the GC-MS analysis revealed several active biocompounds in T. diversifolia and V. lasiopus extracts, which are known for their considerable insecticidal effects. Our data suggest that the organic leaf extracts of T. diversifolia and V. lasiopus have considerable insecticidal properties and would, therefore, be a valuable bioprotective agent for stored maize grains against S. zeamais.